Experimental Film Cooling Effectiveness of Three-Hole-Branch Circular Holes - Fan Yang; Mohammad E. Taslim (International Journal of Rotating Machinery)
A three-hole-branch geometry for film cooling is proposed. Each branch is made up of a streamwise 30°-angled circular hole with a circular hole of the same diameter on each side of it. These three holes share the same inlet area on the coolant supply side. Three side hole inclination angles of 30°, 37.5°, and 45° and three branch angles (the angle between the main and side holes) generated nine configurations that were tested for four blowing ratios of 0.5, 1, 1.5, and 2. To their benefits, these straight-through circular holes could easily be laser drilled on the airfoils or other gas turbine hot section surfaces. For comparative evaluation of these film hole geometries, the commonly used 7°-7°-7° diffusion hole geometry with the same inlet hole diameter was tested as a baseline under otherwise identical conditions. The pressure-sensitive paint (PSP) technique was utilized to test these geometries for their film cooling effectiveness. Depending on the branch geometry, for the same amount of coolant, some configurations were found to be superior to the baseline case for stream- or spanwise film cooling distributions while for the steeper side hole angles, these branched holes did not perform as well as the baseline case. The main conclusion is that the three holes with the same inclination angle of 30° exhibited the best film cooling effectiveness performance including the baseline geometry.